The Influence of Service Quality and Customer Satisfaction on the Trust and Loyalty - Balan Aji Bramantyo; Indrianty Sudirman; Fauziah Umar (Hasanuddin Journal of Business Strategy, 2022)
Loyalty and trust from customers are the keys for the company to be sustainable as when customers are loyal and trust the company, they will make repeat engagement with the company and are reluctant to move with other products and services offered by other companies. The purpose of this study was to determine the effect of service quality and satisfaction on customer trust and customer loyalty of PT. Indonesia National Shipping Company or called PT. PELNI. The study collected data from 98 passengers using the service of the Indonesian National Shipping Company during Covid-19 traveling from Makassar to Bau-Bau or vice versa. Data was collected using questionnaires. Data collected data are then evaluated their validity and reliability and tested their classical assumption test afterward. The study use path analysis to resolve problems raised from the study. The results showed that service quality had a positive and significant effect on consumer trust and loyalty. Satisfaction has a positive and significant effect on customer trust, but an insignificant effect on consumer loyalty. Trust has a positive and significant effect on loyalty.